PENGARUH PELAKSANAAN PEMASARAN TERHADAP LOYALITAS PELANGGAN PADA PLAZA MEBEL FURNITURE CENTER PEKANBARU - Nora, Sri; Heriyanto, Meyzi (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2019)
This study was conducted at Plaza Mebel Furniture Center Pekanbaru which is located on Soekarno Hatta No.89A, Tangkerang Barat, Pekanbaru City, Riau, 28282. This study aims to determine how much influence the product, price, promotion and place on customer loyalty. Samples were taken by 100 respondents and techniques used pusposive Sampling. The data in this study using a survey through questionnaires filled out by customers. The data were obtained using multiple regression analysis. The results showed a significant effect on product Customer Loyalty. Promotion significant effect on Customer Loyalty. Price significant effect on Customer Loyalty. Place significant effect on Customer Loyalty. And simultaneously Product, Promotion, Price and Place significant effect on Customer Loyalty.Â Keywords: Product, Promotion, Price, Place, Customer Loyalty.